QUESTIONING THE ARTICLE ON POLYGAMY REQUIREMENTS FOR THE STATE CIVIL APPARATUS IN INDONESIA (Policy Review Based on Mashlahah Mursalah) - Hamzah, Hamzah; Widodo, Panggih; Wuliana, Wella; Hasida, Hasida (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This article discusses the requirements for polygamy for State Civil Servants in Indonesia which are embodied in Government Regulations which will be reviewed from the perspective of the mashlahah mursalah content of these regulations. This research is a descriptive qualitative research type of library research using primary and secondary data and using content analysis methods in analyzing the data. The results of this research are first, the Indonesian government issued regulations regarding polygamy requirements for State Civil Servants which were embodied in Government Regulation Number 10 of 1983 and then underwent slight changes through Government Regulation Number 45 of 1990. Second, if these regulations are viewed through the lens of mashlahah mursalah, so it can be seen that there are various benefits from this policy, both for the person concerned and for his family, including benefits from an economic, psychological and social perspective. Third, the existence of these regulations is aimed at keeping the performance of the State Civil Service stable by avoiding various family problems if they practice polygamy. The author hopes that this article will provide more serious implications for attention, especially for State Civil Servants who have plans to practice polygamy. So that they can carefully consider this step.